Evaluation of Phytochemicals, and Pharmacological Efficiency Studies of Nyctanthes Arbor-Tristis Linn: Pharmaceutical sciences- Pharmaceutical - Kiruba, Ponnusamy; Palanisamy, Kuppusamy; Selvamaleeswaran, Ponnuswamy; Soundra Rani, Michael Helan; Wesely, Edward Gnanaraj (International Journal of Life Science and Pharma Research, 2023)
Nyctanthes arbor-tristis is a member of the Oleaceae family with various therapeutic characteristics. Different plant components are used intraditional medicine to treat illnesses such as sciatica, chronic fever, and skin diseases. It is today regarded as a rich source of numerous uniquecompounds for creating medicines against various diseases and certain industrial products. In general, the leaves, roots, flowers, and seeds of Parijatare used to cure several ailments in various dose forms, including juice and powder. The current paper discusses the Plant Profile of N. arbor-tristisLinn., as well as the Phytochemical Screening of Extract of N. arbor-tristis Leaves, physicochemical parameters, and the Extraction Procedure andPharmacological Activities conducted on N. arbor-tristis Leaves. The study aims to analyze the antioxidant, antibacterial, and anti-inflammatory potentialof petroleum ether extract of N. arbor-tristis leaves. DPPH scavenging assays and in vitro anti‐inflammatory activity was evaluated using Albumindenaturation, Proteinase inhibitory assay and was subjected to GC-MS analysis to identify its active components. The antibacterial potential wasanalyzed using the agar well diffusion method against Gram-negative and Gram-positive bacteria. Preliminary phytochemical screening confirmed thepresence of alkaloids, flavonoids, phenols, tannins, triterpenoids, Amino acids, Carbohydrate, and the absence of alkaloids, Anthraquinone, Phenols,Saponin, and tannin. Remarkably, free radicals scavenging ability was observed in DPPH with the IC50 of 610.71±13.6μg/mL, and the anti-inflammatoryassay also observed Albumin denaturation with the IC50 of 781.93±13.6μg/mL and the proteinase inhibitory activity with the IC50 of 652.98±32.5μg/mL.In the antibacterial assay, the zone of inhibition was recorded as 20.6±1.6mm, 21.3±1.8mm, 21.3±1.8mm, and 17.9±1.5mm for the strains of Escherichiacoli, Klebsiella pneumonia, Pseudomonas spp., Staphylococcus aureus, and Bacillus spp. respectively. The highest inhibition zone was observed against E. coli(24.8±1.7 and 26.6±1.4mg/mL, respectively), and the least inhibitory was observed against L. acidophilus (19.5±1.1 and 21.7±1.7mg/mL) respectively.GC-MS profile exhibited the presence of 29 components highly accountable for its pharmaceutical activities. The results suggested the presence ofphytochemicals in Nyctanthes arbor-tristis Leaves possess antioxidant and anti-inflammatory properties in the petroleum ether extract. This informationcan be used as a starting point in the search for natural-based drugs that are effective at alleviating inflammatory symptoms and antioxidant aspects.Keywords: , , , , , ,